Clear cell carcinoma of cervix in post-menopausal female (Nepal Journal of Obstetrics and Gynaecology, 2019)
Clear cell carcinoma of cervix is a rare neoplasm accounting for round 4% of all adenocarcinomas. It is usually seen in patients with a history of intrauterine exposure to diethylstilbestrol. We are reporting a case of clear cell carcinoma of cervix in a 50 years old P1L1 postmenopausal woman, with no history of exposure to diethylstilbestrol in-utero or synthetic non-steroidal estrogen, and who was managed with neoadjuvant chemotherapy followed by modified radical hysterectomy with pelvic lymphadenectomy and adjuvant chemotherapy.